Purification and identification of an IgE suppressor from strawberry in an in vitro immunization system - Iwamoto, Akira (Springer Netherlands, 2012)
We purified and identified an IgE suppressor from the strawberry ‘Toyonoka’, based on the decrease of IgE production in in vitro immunization (IVI). Gel filtration experiment indicated that fractions in a 15–48 kDa range and <10 kDa have an IgE suppressive activity. Furthermore, the fraction in 15–48 kDa was subjected to chromatofocusing and found to have activities at isoelectric points, pI 6.0, 7.0, and 8.0–9.2. We focused on the active fractions of pI 8.0–9.2 and the purified a large amount of strawberry extracts by cation exchange resins in batch. A purified 39 kDa protein showed homology to plant glyceraldehyde-3-phosphate dehydrogenase (GAPDH) in N-terminal amino acid sequence and had GAPDH enzymatic activity. Nucleotide sequence and deduced amino acid sequence of the obtained cDNA clone of the protein matched with the sequence of Fragaria x ananassa GAPDH in the GenBank with >98% identical nucleotides and >99% identical amino acids, respectively. The purified strawberry GAPDH suppressed total IgE production in IVI in a dose-dependent manner. From these results, we identified GAPDH as IgE suppressor in the strawberry. Our study may be applicable to the development of new methods to relieve allergic conditions using GAPDH and the screening of other functional factors for human health.